IMPLEMENTASI PENGELOLAAN KEBIJAKAN PENGALOKASIAN DANA PAJAK DARI DANA BAGI HASIL ATAS PAJAK KENDARAAN BERMOTOR TERKAIT PERUNTUKANNYA DI PROVINSI SULAWESI UTARA - George, Stevany Carla Sophia; Pangemanan, Sifrid S.; Wokas, Heince (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
This research discusses about the implementation of earmarking tax on motor vehicle taxes policy that take study in the province of North Sulawesi. This research uses descriptive interpretative and qualitative method research. The purpose of this study are to know how about earmarking tax on motor vehicle tax policy and how to manages earmarking tax on motor vehicle tax in North Sulawesi. The result of this study are earmarking tax on motor vehicle tax policy already in accordance with the provisions ofÂ  Local Regulations year 2011 No. 7, the amount uses of funds to purchase the upgrading of roads maintenance has exceeded at least 10% of motor vehicle taxes. The budgets used on this tax sectors such as the programs of constructions and improvements of regional roads in North Sulawesi already include with the 10% of earmarking tax on motor vehicle tax although 90% of budget comes ftom the APBD.Keywords : Earmarking Tax, Motor Vehicle Tax